Hjem og boskikk - Bing, Morten (Tidsskrift for kulturforskning, 2009)
This article discusses the relationship between interior design, home life and class by introducing the concepts of home life practice (boskikk) and key artefact. A typology of class conditioned home life practice is presented, and illustrated with examples from residences in Kristiania/Oslo in the period 1870-1965.